The principles of artificial intelligence (AI) from a technical perspective (Discourse of Law and Administration, 2025)
The introduction to the topic presented in this article includes theoretical definitions of artificial intelligence and the fields of science that encompass this topic. The following section discusses the structure of an expert system (ES) as a form of implementing artificial intelligence functions in solving various decision-making problems. Particular attention is paid to the application of AI in administrative law. 1 The presentation of the functions and principles of operation of an expert system includes a discussion of individual system elements, starting with the most important part: the knowledge base, its forms of representation, and the sources for defining its content. Furthermore, the role of the database in the system, its types, and methods for defining its values are discussed. In an expert system, apart from the knowledge base, the reasoning process plays a very important role. The article presents the forms of implementing the reasoning process, their properties, and recommended applications. Furthermore, the impact of the logic used in the reasoning process is analyzed. The article also presents the possibilities of representing artificial intelligence based on non-symbolic knowledge representations, such as neural networks. The summary outlines the direction of research on artificial intelligence being conducted in many centers. It states that scientists are attempting to create an artificial mind by using information about the human mind.
Keywords: structure of an expert system; knowledge base; inference systems; fuzzy logic; artificial neural networks; application of artificial intelligence in legal areas